Exploration through “Dyche”: an indigenous study of Yoikana and That Deadman Dance - Joison, S. Frank; Rathna, P. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Dyche, deals with analysing the psyche of the Dalit – “Dyche” - to redefine Dalit community and empower the victimised psyche of Dalit. The exploration of Dalit historiography and psychology through Dyche substantiates that there is cultural, spiritual and psychological uniformity among Dalits and other Indigenous people of the globe. Hence exploration through “Dyche” towards one’s culture, tradition and identity could edify the cause of psychical wounds and thus could facilitate deliverance to indigenous communities from their marginal predicament and bring back harmony. This paper attempts to apply some features of Dyche, the practical Dalit psyche theory, for studying Dalits, Sami people of Norway and Noongar people of Australian Aborigines and to explore their common life experiences, ethos and common self-assertion for liberation with reference to Indian Dalit writer M.C. Raj’s novel, Yoikana and Australian Aboriginal writer Kim Scott’s novel, That Deadman Dance. The paper also endeavours to differentiate between migrant psyche and indigenous psyche and discuss the compensatory mechanisms “Moralising” and “Open Rebellion” adopted by the Oppressor and the Oppressed respectively in their negotiation with the “other.”